Efficacy and safety of camrelizumab plus apatinib for solid tumors: a meta-analysis - Yu, Ping; Song, Xiaoyu; Li, Yue; Chen, Xuanlong; Zhou, Yuan; Jiang, Fei (Frontiers in Immunology, 2025)
ObjectiveThis study used meta-analysis to explore the efficacy and safety of camrelizumab plus apatinib in the treatment of solid tumors.MethodsPubMed, Embase, web of science, and Cochrane library databases were searched for this study, and the searches were conducted from database creation to August 13, 2025. The minors (methodological index for nonrandomized studies) score was used to evaluate the quality of the included studies, and the meta-package in R4.3.3 was used to analyze the data.ResultThe analysis of 35 publications involving 2224 patients revealed various adverse events and survival outcomes. Adverse events of any grade included anemia (ES=0.446), diarrhea (ES=0.217), hypertension (ES=0.478), proteinuria (ES=0.402), and fatigue (ES=0.328). For grade1-2, adverse events, the effect sizes ranged from 0.146to 0.306. For grade ≥3 adverse events, the effect sizes ranged from 0.004 to 0.065. The Objective Response Rate (ORR) was 40.0%, with a Disease Control Rate (DCR) of 78.0%. Overall Survival (OS) rates at 6, 12, and 24 months were 79.0%, 46.5%, and 16.0%, respectively. Progression-Free Survival (PFS) rates at the same intervals were 48.4%, 19.8%, and 6.7%.ConclusionAccording to the results of this meta-analysis, although the camrelizumab plus apatinib treatment regimen demonstrated certain efficacy in the short term, due to the significant limitations of this study, more high-quality, multicenter, large-sample randomized controlled studies are needed in the future to corroborate our conclusions.